Reimagining Girlhood in White Settler-Carceral States. Issue 3 (1st December 2019) - de Finney, Sandrina; Krueger-Henney, Patricia; Palacios, Lena
Abstract : We are deeply honored to have been given the opportunity to edit this special issue of Girlhood Studies, given that it is dedicated to rethinking girlhood in the context of the adaptive, always-evolving conditions of white settler regimes. The contributions to this issue address the need to theorize girlhood—and critiques of girlhood—across the shifting forces of subjecthood, community, land, nation, and borders in the Western settler states of North America. As white settler states, Canada and the United States are predicated on the ongoing spatial colonial occupation of Indigenous homelands. In settler states, as Eve Tuck and K. Wayne Yang remind us, "the settler never left" (2012: 20) and colonial domination is reasserted every day of active occupation. White settler colonialism functions through the continued control of land, resources, and racialized bodies, and is amalgamated through a historical commitment to slavery, genocide, and the extermination of Indigenous nationhood and worldviews. Under settler colonial regimes, criminal justice, education, immigration, and child welfare systems represent overlapping sites of transcarceral power that amplify intersecting racialized, gendered, sexualized, and what Tanja Aho and colleagues call "carceral ableist" violence (2017: 291). This transcarceral power is enacted through institutional and bureaucratic warfare such as, for example, the Indian Act, the school-to-prison pipeline, and the child welfare system to deny, strategically, Indigenous claims to land and the citizenship of racial others.